Improving Vocational Skills and Reducing Textile Waste through Sashiko-Based Community Training: A Social Return on Investment Analysis - Deltu Ariesa; Gancar Candra Premananto; Nur Atika Rochmah; Deny Aditya Pratama; Eunike Dwimilten; Alessandra Natasya Panie (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: The Wastra Bumi Community Development Program addresses textile waste as a social and environmental issue by empowering local communities through the Japanese Sashiko technique. The initiative promotes circular economy practices and Creating Shared Value (CSV) by transforming discarded fabrics into wearable art. The program focuses on underprivileged groups, vocational students, and small creative industries to support sustainable livelihoods and waste reduction. Purpose of the Study: To evaluate the social, environmental, and economic impacts of the Wastra Bumi program using the Social Return on Investment (SROI) approach. Methods: The study involved 20 stakeholders and collected data through field observation, surveys, financial records, and interviews, monetized using national and international proxies. Results: The program generated an SROI ratio of 6.29:1 within one year and 16.62:1 over a three-year projection. The program engaged 240 vocational students and diverted approximately 550 kg of textile waste. It demonstrates that vocational training and multi-sector collaboration deliver strong socio-environmental value. These findings highlight the effectiveness of community-based circular economy interventions in generating measurable and scalable social impact.